Morphology and behaviour of the larva of Calindoea trifascialis (Lepidoptera: Thyrididae), a chemically-defended retreat-building caterpillar from Vietnam - Darling, D. Christopher (Zootaxa, 2003)
The final- instar larva of Calindoea trifascialis is described and illustrated for the first time, including chaetotaxy. All instars have paired fleshy lateral protuberances associated with large exocrine glands on the first abdominal segment. When disturbed, the larvae secrete defensive allomones that deter ants. The larvae construct tent-like feeding retreats and skeletonize the leaves of Dipterocarpus tuberculatus while concealed within the retreat; retreats of increasing size are constructed throughout larval development. When feeding is completed, the final-instar larva constructs a pupation retreat. This leaf roll falls from the plant and is capable of movement prior to pupation. The morphology and larval retreats of an unidentified species of thyridid from Queensland, Australia are also illustrated and discussed in the context of the new information concerning C. trifascialis.